Pain Management for Unconscious Patient Based on Indonesian Nursing Intervention Standards in Intensive Care Unit : Case Study - Meideline Chintya; Henny Batubara; Etika Emaliyawati (Universitas Padjadjaran, 2022)
Introduction: Pain is a subjective thought and can be experienced by everyone. Patients with decreased consciousness may also feel pain. The intensity of pain experienced by patients in the intensive care unit ranges from moderate to severe pain. Previous studies stated that the phenomenon of pain in patients can cause physical and psychological complications. Thus, pain management in the scope of intensive care is crucial to do. Purpose: To identify management that can be done in patients with unconsciousness who experience pain. Methods: This case study used Indonesian Nursing Intervention Standards as a guideline for pain management. Results: A 29-year-old female patient with decreased consciousness was treated in the intensive care unit. The patient was in the intensive care unit for four months. The results showed a severe pain scale at the time of the assessment using the CPOT. This study established a nursing diagnosis of chronic pain related to treatment procedures characterized by a severe pain scale using the CPOT, invasive devices, and the presence of fourth-degree pressure sores on the sacrum. Conclusion: Pain management carried out is pain assessment, non-pharmacological and pharmacological management. In each of these interventions, nurses must pay attention to nursing ethics. Evaluation and documentation are carried out to review the interventions' effect and become a part of communication for interprofessional regarding the treatment process.Keywords: ICU settings, pain management, unconscious patient,